Rapid Increase of Health Care Utilization and Cost due to Benign Prostatic Hyperplasia in Korean Men: Retrospective Populationbased Analysis Using the Health Insurance Review and Assessment Service Data - 손환철; 박준현; 송상훈; 강정윤; 홍성규; 이현무; 김선희; 박병주; 이형래; 이경섭 (Journal of Korean medical science, 2015)
Using the Korean public health insurance database, we analyzed patients diagnosed asbenign prostatic hyperplasia (BPH) from 2004 to 2008. Age and year-specific amount andseasonal variation of hospital visits (HV), duration of treatment (DT), the total and percapita amount of insurance payment (TAIP, PCIP) were evaluated. A total of 12,088,995HV were studied. Total HV increased 1.7 times and DT almost doubled in 2008 compared tothose in 2004. HV, DT, and TAIP showed linearly increasing patterns year by year. In a timeseries analysis, HV increased in winter and demonstrated seasonality in a 12-month cycle. In a Poisson regression analysis, the annual variations of HV, DT, TAIP, and PCIP weredifferent by age groups. In patients older than 40 yr, HV significantly increased 1.10-1.16times compared to that of the previous year. DT markedly increased in their 60s and 80spatients. The rate of increase in PCIP was steeper in patients 50 yr and older than in theothers.Health care utilization due to BPH was rapidly increasing in Korea and it wasremarkable in the elderly population. Seasonal variation of HV demonstrated that healthcare utilization increased in winter. KCI Citation Count: 4